factorise p^2-4pq+4q^2-r^2
Answers
Answered by
25
(p2-4pq+4q2)-r2
(p-2q)2-r2 this is identity of a2-b2
(p-2q-r)(p-2q+r)
(p-2q)2-r2 this is identity of a2-b2
(p-2q-r)(p-2q+r)
Answered by
85
Hi,
p² - 4pq + 4q² - r²
= [ p² - 2 × p × 2q + ( 2q )² ] - r²
= ( p - 2q )² - r²
_________________________
By using the algebraic identity ,
a² - b² = ( a + b ) ( a - b )
_______________________
= ( p - 2q + r ) ( p - 2q - r )
I hope this helps you.
:)
p² - 4pq + 4q² - r²
= [ p² - 2 × p × 2q + ( 2q )² ] - r²
= ( p - 2q )² - r²
_________________________
By using the algebraic identity ,
a² - b² = ( a + b ) ( a - b )
_______________________
= ( p - 2q + r ) ( p - 2q - r )
I hope this helps you.
:)
Similar questions